Prediksi Financial Statement Fraud melalui Fraud Triangle Theory - Nyimas Siti Sarah Ahmadiana; Nova Novita (STIE Indonesia Banking School, 2018)
This study aims to predict the opportunity for companies to commit fraud in financial reporting by using fraud triangle theory. The sample used in this study was 263 non-financial companies. The potential for fraudulent financial reporting is measured using the Beneish M-Score. The component of the fraud triangle theory used is financial pressure, opportunity, and rationalization. The aspect of financial pressure is measured using financial stability, external pressure, personal financial needs, and financial targets. Opportunity aspects are measured using the nature of industry, ineffective monitoring and organizational structure, while aspects of rationalization are measured using change auditors, auditor reports and total accruals. The results showed that financial stability, the nature of the industry and rationalization can be used in predicting opportunities for companies to commit financial reporting fraud.